2014
DOI: 10.3892/ol.2014.2799
|View full text |Cite
|
Sign up to set email alerts
|

Secondary cancer in a survivor of Hodgkin’s lymphoma: A case report and review of the literature

Abstract: Hodgkin’s lymphoma (HL) is one of the most curable malignant diseases in adults. However, HL patients have a higher risk of developing second malignancies compared with the general population. The population of adult cancer survivors is growing, thus, the long-term effects of cancer treatment, including secondary cancer development, have become an increasingly important concern in the field of oncology. The current study presents the case of a female HL survivor who developed two secondary malignancies within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Hodgkins lymphoma survivors treated with radiotherapy are at an increased risk of developing breast, thyroid, lung and colorectal cancers. Patients treated with combination chemotherapy are more prone to develop secondary leukemias (15,16) . Lung cancer patients are more prone to develop second malignancies which are related to smoking (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Hodgkins lymphoma survivors treated with radiotherapy are at an increased risk of developing breast, thyroid, lung and colorectal cancers. Patients treated with combination chemotherapy are more prone to develop secondary leukemias (15,16) . Lung cancer patients are more prone to develop second malignancies which are related to smoking (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated for Hodgkin's lymphoma (HL), which is often diagnosed at an early age, have a higher risk of developing secondary tumors associated with their treatment (radiotherapy and chemotherapy). After radiotherapy the following are observed with greater frequency: breast cancer, lung cancer, and thyroid cancer [16,17]; and following chemotherapy: leukemia, lung cancer, gastrointestinal cancer, and sarcoma [18]. In 2006 Franklin, et al reported that the application of chemotherapy and radiotherapy in the treatment of HL increases the risk of developing secondary tumors [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, recently reviewed by Lisik-Habib and coworkers (6), assessed or quantified the risk of developing secondary cancers following the successful treatment of HL. However they failed in producing consistent results, possibly due to differences in the number of patients included in the analysis, the characteristics of the study population, the length of the follow-up period, the chemotherapy schedule, the age of HL diagnosis and the dose and volume of irradiation (6). To our knowledge, this is the first case report, according to the scientific literature, of caecal leiomyoma developing after chemotherapy in a HL survivor.…”
Section: Discussionmentioning
confidence: 99%